2018
DOI: 10.1093/nar/gky797
|View full text |Cite|
|
Sign up to set email alerts
|

Developmental and cancer-associated plasticity of DNA replication preferentially targets GC-poor, lowly expressed and late-replicating regions

Abstract: The spatiotemporal program of metazoan DNA replication is regulated during development and altered in cancers. We have generated novel OK-seq, Repli-seq and RNA-seq data to compare the DNA replication and gene expression programs of twelve cancer and non-cancer human cell types. Changes in replication fork directionality (RFD) determined by OK-seq are widespread but more frequent within GC-poor isochores and largely disconnected from transcription changes. Cancer cell RFD profiles cluster with non-cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…Accordingly, we did not observe a coding strand bias within the 44 classified mutations (Additional file 1 : Table S1) and most of the APOBEC-associated hotspots preferentially occurred in lagging-strand templates during DNA replication compared to those non APOBEC-associated hotspot mutations (Fig. 2 a, across 9 cell lines [ 37 , 38 ], ‘ Methods ’). Additionally, DNA folding predictions indicated that the APOBEC-associated hotspots were preferentially located within the loop of DNA hairpin structures compared to non APOBEC-associated ones (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Accordingly, we did not observe a coding strand bias within the 44 classified mutations (Additional file 1 : Table S1) and most of the APOBEC-associated hotspots preferentially occurred in lagging-strand templates during DNA replication compared to those non APOBEC-associated hotspot mutations (Fig. 2 a, across 9 cell lines [ 37 , 38 ], ‘ Methods ’). Additionally, DNA folding predictions indicated that the APOBEC-associated hotspots were preferentially located within the loop of DNA hairpin structures compared to non APOBEC-associated ones (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…We performed analysis of published genome-wide replication fork directionality (RFD) data in nine human cancer/normal cell lines—HeLa, IMR90, TLSE19, K562, TF1, GM06990, BL79, IARC385 and Raji cells [ 37 , 38 ]—to identify the strand that would be favoured as the lagging-strand template. Considering APOBEC enzymes specifically deaminated ‘C’ to ‘U’, we expected the complementary strand to be the lagging-strand template if mutations were of the N G A → N [ C / A ] A type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After confirming the validity of the ChIP experiments and establishing an analysis approach based on moderate averaging, we compared the relative read frequencies of each pre-RC component to active replication initiation units. Using OK-seq in Raji cells 37 , we calculated the replication fork directionality (RFD), and delineated zones of preferential replication initiation as ascending segments (AS) of the RFD profile. OK-seq does not detect single replication initiation events, but regions of preferential replication initiation (AS) 22, 24, 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Raji OK-seq was recently published as part of Wu et al . and is available from the European Nucleotide Archive under accession number PRJEB25180 (see data access section) 37 . Reads > 10 nt were aligned to the human reference genome (hg19) using the BWA (version 0.7.4) software with default parameters 60 .…”
Section: Methodsmentioning
confidence: 99%